Application and Research of RE in AutoCAD System - Li Shi, Zhanbo Liu, Jia Fu, Shi Yan (Forest Chemicals Review, 1970)
With the development of science and technology, the application of Reverse Engineering Technology Reverse Engineering in machinery and other fields has become the frontier science in the field of science and technology today. In order to improve the production efficiency and shorten the product development cycle, the processing of data on the basis of existing sample images has become an inevitable trend in the development of the mechanical field today. In this paper, we analyze the method of contour line tracing of the scanned drawing by applying the reverse engineering technology, and elaborate the design theoretical idea and its implementation process of the CAD 3D model system generated from the scanned drawing by using AutoCAD and VB.NET as the development environment. Combined with the scanned drawing of a mechanical part gear as an example, the scan drawing generation 3D modeling system is successfully used to realize 3D modeling.